Characterization of Zeolite-Based Coatings for Adsorption Heat Pumps - Freni, A (Springer, 2016)
This book proposes a radically new approach for characterizing thermophysical and mechanical properties of zeolite-based adsorbent coatings for Adsorptive Heat Transformers (AHT). It presents a developed standard protocol for the complete characterization of advanced coated adsorbers. Providing an in-depth analysis of the different procedures necessary for evaluating the performance of adsorbers, it also presents an analysis of their stability under the hydrothermal and mechanical stresses during their entire life cycle.